4x-8-2x+3=-10x+7+12x+5

Simple and best practice solution for 4x-8-2x+3=-10x+7+12x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-8-2x+3=-10x+7+12x+5 equation:


Simplifying
4x + -8 + -2x + 3 = -10x + 7 + 12x + 5

Reorder the terms:
-8 + 3 + 4x + -2x = -10x + 7 + 12x + 5

Combine like terms: -8 + 3 = -5
-5 + 4x + -2x = -10x + 7 + 12x + 5

Combine like terms: 4x + -2x = 2x
-5 + 2x = -10x + 7 + 12x + 5

Reorder the terms:
-5 + 2x = 7 + 5 + -10x + 12x

Combine like terms: 7 + 5 = 12
-5 + 2x = 12 + -10x + 12x

Combine like terms: -10x + 12x = 2x
-5 + 2x = 12 + 2x

Add '-2x' to each side of the equation.
-5 + 2x + -2x = 12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 + 0 = 12 + 2x + -2x
-5 = 12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 = 12 + 0
-5 = 12

Solving
-5 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 42s+s=8322 | | 4(4x-9)+9x= | | 9x+6(80)=7x+560 | | 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 | | x*0.022=1 | | 12y-13=7y+12 | | 4-23=8x-6-7x | | 2(3x)+5x=770 | | 2x+11=21-3x | | 10x=20.2 |

Equations solver categories